Sifat Kimia dan Dimensi Serat Kayu Mangium (Acacia mangium Willd.) dari Tiga Provenans. Chemical Properties and Fiber Dimension of Acacia mangium Willd. from Three Provenances - Wasrin Syafii; Iskandar Z Siregar (Jurnal Ilmu dan Teknologi Kayu Tropis, 2006)
The objectives of this research are to evaluate the chemical components and the fiber dimension of Acacia mangium Willd from three provenances.  The wood samples used in this study are grown in Parungpanjang, Bogor originated from three provenances namely Queensland (QLD), Papua New Guinea (PNG), and East Indonesia (EI). The chemical components measured in this study are cellulose, hemicelluloses, lignin, and extractives, while fiber dimensions and its derivatives determined are Runkle Ratio, Felting Power, Muhlsteph Ratio, Flexibility Ratio, and Coefficient of Rigidity. This research indicated that among three provenances investigated, the Queensland provenance is better than two others as sources of raw material for pulp and paper due to the highest cellulose content and lowest lignin and extractives contents. Likewise, from fiber dimension aspect, Queensland provenance also showed better properties than that of PNG and EI